Identifikasi Gaya Belajar Mahasiswa Calon Guru IPA Universitas Negeri Makassar - Yanto, Nurfitra; Muhiddin, St. Mutia Alfiyanti; Syakur, Akhmad; Arsyad, Arie Arma (SAINTIFIK, 2024)
Student learning style is one of the important things that teachers need to know before carrying out the learning process. So that teachers can determine the appropriate learning process for the class. This study uses quantitative descriptive which aims to identify the learning styles of prospective science teachers. The research sample amounted to 71 students of class 2022 Science Education FMIPA UNM. The research instrument used was a questionnaire with 30 statement items with 5 scales. This learning style focuses on visual, auditory, and kinesthetic. The results showed that overall, dominant students had a visual learning style.